SIFAT FISIK KAYU LAPIS BERBAHAN BAKU KAYU AKASIA (Acacia mangium Willd) DAN KELAMPAYAN (Anthocephalu spp) - Arsad, Effendi (Jurnal Riset Industri Hasil Hutan, 2011)
The utilization of acacia and kelampayan wood as  plywood materials  were done. There are two kinds of treatments with two cores samples.  Wood core with thickness 2 mm and 3 mm with the spreading rate of adhesive  150 gr/m2, 200 gr/m2 and 250 gr/m2.   Resuls showed  that the  water content  of plywood  are 9,01% - 14,29%  for acacia and 9,17% - 10,58%   for kelampayan wood material.  The density of the plywood are 0,62 gr/cm3 – 0,73 gr/cm3  for acacia and 0,44 gr/cm3 – 0,57 gr/cm3.  for kelampayan wood material.  The tensile  strength of plywood are tensile strength of  plywood  are 9,49 kg/cm2 – 14,73 kg/cm2  for acacia and 8,61 kg/cm2 – 12,58 kg/cm2   for kelampayan wood material.Keywords: acacia, kelampayan,  the spreading rate of adhesive,  physics       characteristic,  plywood